Professional Preferences and Professional Identity in Engineering Students from a Private University in Arequipa - Arias Gallegos, Walter L. (2019)
The present study analyzes the professional preferences in students of four engineering careers from a private university in Arequipa City, in relation to some aspects of professional identity. To that end, we took a sample of 422 students of Industrial Engineering, Electronic and Telecommunications Engineering, Civil Engineering and Computing Science. We applied two instruments: the Pereira’s Professional Preferences Profile and the Professional Identity Questionnaire of Arias et al. The results indicate that the engineering students have professional preferences according to its professional field, but a considerable percentage is located in the category of non-defined (24.17%). Moreover, the 18.22% of students of Industrial Engineering have professional preferences for Business Administration, and the majority of them have a professional identity with scientific and technical orientation, regarding object of study, methods and professional goals.